Data from: Herbivore resistance in congeneric and sympatric Nothofagus species is not related to leaf habit - Piper, Frida I.; Gundale, Michael J.; Fuenzalida, Tomás; Fajardo, Alex (2019)
Premise of the study Two fundamental hypotheses on herbivore resistance and leaf habit are the resource availability hypothesis (RAH) and the carbon-nutrient balance hypothesis (CNBH). The RAH predicts higher constitutive resistance by evergreens and the CNBH predicts higher induced resistance by deciduous species. Although support for these hypotheses is mixed, they have rarely been examined in congeneric species. Methods We compared leaf constitutive and induced resistance (as leaf polyphenols and tannin concentrations, and damage level in non-choice experiments) and leaf traits associated with herbivory of coexisting Nothofagus species using 1) a defoliation experiment, and 2) a natural defoliation caused by an outbreak of a common defoliator of Nothofagus species. Key Results In the defoliation experiment, polyphenol and tannin concentrations were similar between deciduous and evergreen species; regardless of leaf habit, polyphenols increased in response to defoliation. In the natural defoliation survey, N. pumilio (deciduous) had significantly higher herbivory, lower C/N ratio and leaf mass per area, and higher nitrogen and phosphorous concentrations than N. betuloides (evergreen); N. antarctica (deciduous) had intermediate values. Polyphenol concentrations and herbivore resistance indicated by the non-choice experiment were lower in N. pumilio than in N. antarctica and N. betuloides, which had similar values. Conclusions Higher herbivory in N. pumilio was associated with a higher nutritional value and a lower level of leaf C-based defenses compared to both the evergreen and the other deciduous species, indicating that herbivore resistance in Nothofagus species cannot be attributed to only leaf habit as predicted by the RAH or CNBH. Please be aware that if you ask to have your user record removed, we will retain your name in the records concerning manuscripts for which you were an author, reviewer, or editor. In compliance with data protection regulations, you may request that we remove your personal ...